Performance Evaluation of Solar Photovoltaic Thermal Air Collector Based on Energy and Exergy Analysis (The International Journal of Engineering & Information Technology (IJEIT), 2024)
This work presents a comprehensive parametric study of thermal and electrical performance of four different designs of photovoltaic/ thermal air heaters (PV/T) based on energy and exergy analysis. The results are compared to that from the conventional design of flat duct PV/T. The main goal of these designs is to enhance the heat transfer inside the air duct and consequently to increase the system's electrical power output. A computer simulation program has been developed in order to calculate the electrical and thermal PV/T collector parameters. The results indicate that an increase of 52, 52.4, and 68.25 % in the total system efficiency has been achieved from the corrugated duct, double pass design and finned duct respectively. Furthermore, at a low mass flow rates the electrical efficiency has also been improved for the three types by 9.8, 14.6 and 12.6 % respectively compared to that of flat duct design. The temperature of the PV arrays has a major effect on the exergy efficiency and removing heat from the PV module keeps the net power output at satisfactory level.